Meningkatkan Aktivitas Belajar Bahasa Indonesia Melalui Model Pembelajaran Pertemuan Kelas Pada Kelas V SDN 3 Pekanbaru - Desriana Sovia; Nursalim Nursalim (el-Ibtidaiy:Journal of Primary Education, 2020)
This study aims to describe the increase in studen learing activities on Indonesia language lessons through the application of learning models for class meetings  in class V SDN 3 Pekanbaru. The study was mitivated by the low of students’ activities at Indonesian Language subject. The problems ware caused by some factors : the teacher used Monotonous way in teaching, the students were diffuclt in understanding the Subject, the were shy in delivering their ideas, the students were playing With their friend in studying, the students did not focus on studying, and they have Low interest instudy. The formulation of study were whether the use class meeting Learning model increased learning activities of Indonesian language at the fifth Year students of state elementary school 3 Pekanbaru.The study was done into two cycles, the first cycle and the second cycle were done into one meeting. For the success of study the writer arranged the following stages namely: 1) the preparation of action, 2) the implementation of action, 3) observation, 4) reflection.The success of class meeting model was known on the improvement of students’ learning activities in Indonesia language subject prior action at the first cycle and at the second cycle. Students’ learnig activities at prior action was categorized “low” as the number of 59 was in the range 45-64 and the average was 58,9%. At the first cycle students’ learning activities was categorized “enough” as the score 66 was in the range 65-74 and the average was 66,1%. At the second cycle students’ learning activities was categorized “very good” because the number 89 was in the range of 85-100 and the average was 88.7%. this means that class meeting learning model improved students’ learning activities of Indonesia language at the fifth year students of state elementary school 3 Pekanbaru.